Bhutanese or Nepali? The Politics of Ethnonym Ambiguity. Issue 4 (4th July 2021) - Nelson, Andrew; Stam, Kathryn
Abstract: For the group of Nepali-speaking refugees who fled Bhutan in the early 1990s, there exists no consensus ethnonym, but rather multiple terms—'Nepali', 'Bhutanese' and 'Lhotshampa'. Based on a mixed methods approach, this article addresses the politics of ethnonym ambiguity by contextualising current naming practices within the group's legacy of displacement as migrants in Bhutan and refugees in Nepal. In resettlement in the United States, refugees translate this legacy into strategic identification with both Bhutan and Nepal as a form of negotiation with new contexts of ambiguity conditioned by the politics of 'deserving-ness', racialisation and diaspora.